The effect of Pt nanoparticles loading on H2 sensing properties of flame-spray-made SnO2 sensing films - Liewhiran,C. (Elsevier BV, 2015)
SnO2 nanoparticles loaded with 0.2-2 wt% Pt have successfully been synthesized in a single step by flame spray pyrolysis (FSP) and investigated for gas sensing towards hydrogen (H2). According to characterization results by X-ray diffraction, nitrogen adsorption, scanning/high resolution-transmission electron microscopy and analyses based on Hume-Rothery rules using atomic radii, crystal structure, electronegativities, and valency/oxidation states of Pt and Sn, it is conclusive that Pt is not solute in SnO2 crystal but forms nanoparticles loaded on SnO 2 surface. H2 gas sensing was studied at 200-10,000 ppm and 150-350 °C in dry air. It was found that H2 response was enhanced by more than one order of magnitude with a small Pt loading concentration of 0.2 wt% but further increase of Pt loading amount resulted in deteriorated H2-sensing performance. The optimal SnO2 sensing film (0.2 wt% Pt-loaded SnO2, 20 μm in thickness) showed an optimum H2 response of ∼150.2 at 10,000 ppm and very short response time in a few seconds at a low optimal operating temperature of 200 °C. In addition, the response tended to increase linearly and the response times decreased drastically with increasing H2 concentration. Moreover, the selectivity against carbon monoxide (CO) and acetylene (C 2H2) gases was also found to be considerably improved with the small amount of Pt loading. The H2 response dependence on Pt concentration can be explained based on the spillover mechanism, which is highly effective only when Pt catalyst is well-dispersed at the low Pt loading concentration of 0.2 wt%. © 2014 Elsevier B.V. All rights reserved.